Central Role of Adenosine 5′-Phosphosulfate Reductase in the Control of Plant Hydrogen Sulfide Metabolism - Fu, Yang; Tang, Jun; Yao, Gai-Fang; Huang, Zhong-Qin; Li, Yan-Hong; Han, Zhuo; Chen, Xiao-Yan; Hu, Lan-Ying; Hu, Kang-Di; Zhang, Hua (Frontiers in Plant Science, 2018)
Hydrogen sulfide (H2S) has been postulated to be the third gasotransmitter in both animals and plants after nitric oxide (NO) and carbon monoxide (CO). In this review, the physiological roles of H2S in plant growth, development and responses to biotic and abiotic stresses are summarized. The enzymes which generate H2S are subjected to tight regulation to produce H2S when needed, contributing to delicate responses of H2S to environmental stimuli. H2S occupies a central position in plant sulfur metabolism as it is the link of inorganic sulfur to the first organic sulfur-containing compound cysteine which is the starting point for the synthesis of methionine, coenzyme A, vitamins, etc. In sulfur assimilation, adenosine 5’-phosphosulphate reductase (APR) is the rate-limiting enzyme with the greatest control over the pathway and probably the generation of H2S which is an essential component in this process. APR is evolutionarily conserved protein among plants, and two conserved domains PAPS_reductase and Thioredoxin are found in APR. Sulfate reduction including the APR-catalyzing step is carried out chloroplasts. APR, the key enzyme in sulfur assimilation, is mainly regulated at transcription level by transcription factors in response to sulfur availability and environmental stimuli. The cis-acting elements in the promoter region of all the three APR genes in Solanum lycopersicum suggests that multiple factors such as sulfur starvation, cytokinins, CO2 and pathogens may regulate the expression of SlAPRs. In conclusion, as a critical enzyme in regulating sulfur assimilation, APR is probably critical for H2S generation during plants’ response to diverse environmental factors.